MOTIVATIONAL STRATEGIES FOR ENHANCING STUDENT LEARNING OUTCOMES IN HIGHER EDUCATION - Nadiah Ismail; Khalid Mahmud; Sonam Lhamo; Tri Budi Rahayu (Yayasan Adra Karima Hubbi, 2026)
Motivational strategies play a crucial role in enhancing student learning outcomes in higher education. As students face increasing academic challenges, effective motivational techniques can foster engagement, persistence, and academic success. However, there is a need for research that identifies and evaluates which motivational strategies are most effective in diverse educational contexts. This study aims to examine the role of various motivational strategies in improving student learning outcomes in higher education. The research seeks to identify strategies that foster intrinsic motivation, enhance student engagement, and ultimately contribute to academic achievement. A mixed-methods approach was used, combining quantitative surveys and qualitative interviews with students and faculty from a range of disciplines. The survey assessed the impact of various motivational strategies, including goal setting, feedback, and active learning techniques, on student performance. Interviews provided deeper insights into how students and instructors perceive and implement these strategies. The findings indicate that goal setting, constructive feedback, and active learning strategies significantly enhance student engagement and performance. Students who reported receiving personalized feedback and setting clear academic goals exhibited higher levels of motivation and academic success. Motivational strategies are essential for improving student learning outcomes in higher education.